Cursus Theologiae Moralis - Maria, R. P. Franciscum a Jesu (1728)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Cursus Theologiae Moralis - Maria, R. P. Franciscum a Jesu (1728)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Cursus Theologiae Moralis - Maria, R. P. Franciscum a Jesu (1728)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Cursus Theologiae Moralis - R.P.F. Franciscum A Jesu Maria (Apud Nicolaum Pezzana, 1728)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover; Religion; Teaching; Theology; USJ SEMINARY LIBRARY PROJECT